Determinant Factors Affecting Public Awareness in Maintaining Dental and Oral Health in Wonokromo and Sawunggaling Subdistricts, Surabaya, East Java - Diajeng Ayu Permatasari Yusuf; Byba Melda; Katmini (Journal of Health Promotion and Behavior, 2024)
Background: Dental and oral health maintainance is one of the most supporting aspects in healthy paradigm, and it’s a national development strategy to create Indonesia’s Healthy life. Dental and oral health among Indonesian people still needs serious attention. Therefore, dental and oral health maintainance needs to be considered. This study aimed to analyze the theory of Health Belief Model (HBM) consisting of knowledge, environment, perceived barriers, perceived susceptibility, perceived benefits, and cues to action on public awareness in maintaining dental and oral health in Wonokromo and Sawunggaling Subdistrics, Surabaya. Subjects and Method: An observational analytic with a cross sectional research design was conducted at Wonokromo and Sawunggaling Subdistricts, Surabaya, East Java from July to September 2022. A total of 400 people were selected for this study. The dependent variable was awareness in maintaining dental and oral health. The independent variables were knowledge, environment, perceived susceptibility, perceived severity, perceived barrier, perceived benefit, and cues to action. The data were analyze using linear regression. Results: Maintaining dental and oral health increased with the environment (b=0.02; p= 0.181), perceived severity (b= 0.01; p= 0.676), perceived benefit (r= 0.007; p= 0.304), and cues to action (r= 0.01; p= 0.181), but statistically not significant. Conclusion: Maintaining dental and oral health increased with environment, perceived severity, perceived, and cues to action, but statistically not significant.